Customer Development Model Dalam Bisnis Jasa Pembelajaran Program English as Second Languange (ESL) - Niken Dyah Wanodyanti; Idqan Fahmi; Agus Maulana (School of Business, Bogor Agricultural University (SB-IPB), 2019)
The purpose of study is to test the application of Customer Development Model (CDM) in a language service business called English as Second Language (ESL). This study uses CDM approach by incorporating business model canvas and SERVQUAL. The study uses qualitative and quantitative approaches by involving corporate clients (headmaster and ESL teacher implementers) and corporate management to perceive consumer perceptions. The results of this study indicate that the company has passed the stage of customer discovery and customer validation for two years. The next stage is the customer creation with the results of a new marketing strategy formulation. The new marketing strategy formulation is a result of the improvement of the business model canvas and the evaluation of the old marketing strategy. The improvement of the canvas business model is derived from customer perception with SERVQUAL method. Formulation of marketing strategy will be conducted using the main strategy of providing holistic services and 7P (product, promotion, price, place, people, process, dan physical evidence) marketing mix strategy. The managerial implications that need to be carried by PT Pendidikan Prima Utama are the improvement of tools, service improvement, and ESL program development.Keywords: business model canvas, CDM, ESL, service business, SERVQUALAbstrak: Tujuan penelitian ini adalah menguji penerapan Customer Development Model (CDM) dalam bisnis jasa dengan kasus program English as Second Languange (ESL). Pendekatan penelitian ini melalui CDM dengan menggunakan model bisnis kanvas dan SERVQUAL. Penelitian menggunakan pendekatan kualitatif dan kuantitatif dengan melibatkan klien perusahaan (kepala sekolah dan guru implementor ESL) dan manajemen perusahaan untuk melihat persepsi konsumen. Hasil penelitian ini menunjukkan bahwa perusahaan sudah melewati tahapan customer discovery dan customer validation selama dua tahun. Tahapan selanjutnya adalah customer creation dengan hasil rumusan strategi pemasaran yang baru. Rumusan strategi pemasaran yang baru merupakan hasil perbaikan model bisnis kanvas dan evaluasi strategi pemasaran yang lama. Perbaikan model bisnis kanvas diperoleh dari hasil persepsi pelanggan dengan metode SERVQUAL. Rumusan strategi pemasaran yang akan dilakukan dengan strategi utama memberikan pelayanan holistik dan strategi bauran pemasaran 7P (product, promotion, price, place, people, process, dan physical evidence). Implikasi manajerial yang perlu dilakukan pada tahap customer creation ini adalah perbaikan perangkat, perbaikan pelayanan, dan pengembangan program ESL.Kata kunci: bisnis jasa, CDM, ESL, model bisnis kanvas, SERVQUAL